Study of Mechanical Properties of Pervious Concrete as a Pavement Material by Partial Replacement of Ggbs in Cement with Addition of Cellulose Fibers - M. Ganesh, K; S. S. Vara Prasad, A; S. Viswa Harish, P; Subrahmanyam Raju, A (International Journal of Engineering and Technology, 2018)
Among all the transportation systems roadways is most commonly used transportation system. But in present scenario roads faces a lot of problems like potholes, cracks and many other distresses. Not even these but water is also the main enemy to the pavement which causes deformations and changes the texture of subgrade soil resulting in large variation in performance.The total Impervious Surface Change (ISC) in India for the decade 2000 to 2010 is 2274.62 km2. This is one of the most considerable problems due to rapid urbanization where there is a tremendous increase in construction of black topped and different types of impervious pavements. This has an adverse effect on the environment as the storm water becomes stagnant over the surface of the pavement due to inadequate drainage conditions.The necessity for reducing stagnation and the surface runoff has given the inception of pervious pavement surface. Pervious concrete pavement is a special type of its kind with high perviousness with no or minimal fines which allow water to percolate through it and thus the water which is accumulated over the surface can be collected and used for various purposes.The present work studied the mechanical properties and also the permeability of pervious concrete of mix 3:1 aggregate cement ratio. The control mix is altered by partially replacing 30% of cement with Ground Granulated Blast furnace Slag (GGBS), included Cellulose fibers of 5% of weight of the cementitious material and combination of both in one mix and compared the results obtained.The properties such as compressive strength, split tensile strength, flexural strength and permeability are assessed by performing tests. It was observed that there is an increase in Compressive Strength, Split Tensile Strength, Flexure Strength and decrease in the permeability in the altered pervious concrete mixes when compared to the Pervious concrete with no additives.Â Â